Analisis Pengaruh Capital Adequacy Ratio, Biaya Operasional dan Pendapatan Operasional Terhadap Return On Asset Perbankan Periode 2021- 2024 : Analysis of the Effect of Capital Adequacy Ratio, Operating Costs, and Operating Income on Return on Assets in Banking for the Period 2021-2024 - Alviani Rahmanda Putri; Tri Lestari (CV Warnak Johanna Nusantara, 2025)
This study aims to analyze the influence of the Capital Adequacy Ratio (CAR) and Operating Expenses to Operating Income (BOPO) on Return On Assets (ROA) in the banking sector listed on the Indonesia Stock Exchange during the 2021–2024 period. The data used are secondary data obtained from the financial statements of 28 main-board banks, which were then analyzed using quantitative statistical methods and quantile regression with the assistance of SPSS version 27. The results of the study indicate that, partially, CAR has a positive and significant effect on ROA, particularly at the median (q=0.5) and upper quantiles (q=0.75), while BOPO does not have a significant effect on ROA across all tested quantiles. The Pseudo R-squared value of 0.171 indicates that the model explains 17.1% of the variation in ROA, with the remaining variation accounted for by other variables outside the model. These findings suggest that although CAR plays an important role in enhancing bank profitability, operational efficiency factors such as BOPO need to be re-examined in the context of their impact on ROA. Further research is recommended by incorporating additional variables to obtain a more comprehensive understanding